Deferred Versus Immediate Stenting in Patients With ST‐Segment Elevation Myocardial Infarction: A Systematic Review and Meta‐Analysis. Issue 3 (8th March 2017) - Qiao, Jianzhong; Pan, Lingxin; Zhang, Bin; Wang, Jie; Zhao, Yongyan; Yang, Ru; Du, Huiling; Jiang, Jie; Jin, Conghai; Xiong, Enlai
Abstract : Background: A number of studies have evaluated the efficacy of deferred stenting vs immediate stenting in patients with ST‐segment elevation myocardial infarction, but the findings were not consistent across these studies. This meta‐analysis aims to assess optimal treatment strategies in patient with ST‐segment elevation myocardial infarction. Methods and Results: We searched the PubMed, EMBASE, and the Cochrane Library for studies that assessed deferred vs immediate stenting in patients with ST‐segment elevation myocardial infarction. Nine studies including 1456 patients in randomized controlled trials and 719 patients in observational studies were included in the meta‐analysis. No significant differences were observed in the incidence of no‐ or slow‐reflow between deferred stenting and immediate stenting in randomized controlled trials (odds ratio [OR] 0.51, 95%CI 0.17‐1.53, P =0.23, I 2 =70%) but not in observational studies (OR 0.13, 95%CI 0.06‐0.31, P <0.0001, I 2 =0%). Deferred stenting was associated with an increase in long‐term left ventricular ejection fraction (weighted mean difference 1.90%, 95%CI 0.77‐3.03, P =0.001, I 2 =0%). No significant differences were observed in the rates of major adverse cardiovascular events (OR 0.53, 95%CI 0.27‐1.01, P =0.06 [randomized OR 0.98, 95%CI 0.73‐1.30, P =0.87, I 2 =0%; nonrandomized OR 0.30, 95%CI 0.15‐0.58, P =0.0004, I 2 =0%]), major bleeding (OR=0.1.61, 95%CI 0.70‐3.69, P =0.26, I 2 =0%), death (OR=0.78, 95%CI 0.53‐1.15, P =0.22, I 2 =0%), MI (OR=0.97, 95%CI 0.34‐2.78, P =0.96, I 2 =35%) and target vessel revascularization (OR 0.97, 95%CI 0.40‐2.37, P =0.95, I 2 =24%), between deferred and immediate stenting. Conclusions: Compared with immediate stenting, a deferred‐stenting strategy did not reduce the occurrence of no‐ or slow‐reflow, death, myocardial infarction, or repeat revascularization compared with immediate stenting in patients with ST‐segment elevation myocardial infarction, but showed an improved left ventricular function in the long term.